Toward sustainability: the role of social entrepreneurship in creating social-economic value in renewable energy social enterprises - Bataineh, Mohammad Jamal; Marcuello, Carmen; Sánchez-Sellero, Pedro (REVESCO. Revista de Estudios Cooperativos, 2023)
This study explores the scope of social entrepreneurship and examines how social entrepreneurship contributes to sustainable development. Using analysis and relevant comparisons, it identifies main actors in the socialenterprise ecosystem, as well as how the entrepreneurial ecosystem adapts to social enterprises. Additionally, this study reveals how social enterprise applies in the renewable energy domain and identifies its main advantages, as well as major barriers and how to overcome those barriers. Fundamentally, this study’s findings have significant implications, for academics and practitioners in the social field. It highlights the role of social entrepreneurship as a balanced approach for long-run increases in quality of life, and it follows innovative techniques and methods to meet social needs, inherently motivated by ethical factors in equality and social fairness. On the other hand, main challenges that could confront social entrepreneurship include government regulations, problems adopting advanced technology and infrastructure, external competitive threats, limited access to public funds or loans, lack of awareness and acquisition of skills and knowledge, and inadequate knowledge about social impact measurement techniques. This research also illustrates how to adapt Isenberg’s model for the entrepreneurial ecosystem in the social enterprises, which shows that the evolution of social enterprises does not occur in a vacuum; rather, the growth of social enterprise ecosystems occurs through interactions and networks with various actors in different fields such as financial politics, law, and academia. Finally, we review the practical applications of social enterprises by highlighting the main benefits of RE social enterprises: energy savings, community awareness, and the creation of favorable social externalities in rural and developing areas.